Crystal structure of tetrakis(O,O′-diisopropyldithiophosphato-κ2S,S′)-(μ2-1,2-bis(4-pyridylmethylene)hydrazine-κ2N:N′)zinc(II), C36H66N4O8P4S8Zn2 - Tan, Yee Seng *; Tiekink, Edward R. T. * (de Gruyter, 2019)
C36H66N4O8P4S8Zn2, triclinic, P¯1 (no. 2), a = 7.94960(10) Å,b = 11.5638(2) Å, c = 16.5616(2) Å, α = 75.604(1)°, β = 86.321(1)°, γ = 83.103(2)°, V = 1463.06(4) Å3, Z = 1, Rgt(F) = 0.0424, wRref(F2) = 0.1072, T = 100(2) K. CCDC no.: 1903609 The molecular structure is shown in the figure. Table 1 contains crystallographic data and Table 2 contains the list of the atoms including atomic coordinates and displacement parameters.